Optimalisasi Pengembangan Pariwisata Desa Melalui Kegiatan Njelajah Mbantul Milang Kori 2024 di Kabupaten Bantul - Hari Rachmadi; Afif, Fuadi; Eko Haryanto (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2025)
Optimization of Rural Tourism Development Through the Njelajah Mbantul Milang Kori 2024 Activities in Bantul Regency The Njelajah Mbantul Milang Kori 2024 activity is a community service effort aimed at introducing and promoting the tourism potential of Bantul Regency, particularly in the Rintisan Kalurahan Budaya (RKB) and Desa Wisata. This activity was carried out through a series of visits to various tourist destinations, involving multiple stakeholders, and focusing on enhancing synergy between local government, tourism practitioners, and the local community. The results of the activity show an increase in awareness and interest of tourists in Bantul's tourism potential, as well as strengthening cooperation among stakeholders in developing local tourism. This activity is expected to serve as a model for similar initiatives in other regions with untapped tourism potential.